Privacy-Preserving Poisoning-Resistant Blockchain-Based Federated Learning for Data Sharing in the Internet of Medical Things - Xudong Zhu; Hui Li (Applied Sciences)
The Internet of Medical Things (IoMT) creates interconnected networks of smart medical devices, utilizing extensive medical data collection to improve patient outcomes, streamline resource management, and guarantee comprehensive life-cycle security. However, the private nature of medical data, coupled with strict compliance requirements, has resulted in the separation of information repositories in the IoMT network, severely hindering protected inter-domain data cooperation. Although current blockchain-based federated learning (BFL) approaches aim to resolve these issues, two persistent security weaknesses remain: privacy leakage and poisoning attacks. This study proposes a privacy-preserving poisoning-resistant blockchain-based federated learning (PPBFL) scheme for secure IoMT data sharing. Specifically, we design an active protection framework that uses a lightweight <semantics>(t,n)</semantics>-threshold secret sharing scheme to protect devices’ privacy and prevent coordination edge nodes from colluding. Then, we design a privacy-guaranteed cosine similarity verification protocol integrated with secure multi-party computation techniques to identify and neutralize malicious gradients uploaded by malicious devices. Furthermore, we deploy an intelligent aggregation system through blockchain smart contracts, removing centralized coordination dependencies while guaranteeing auditable computational validity. Our formal security analysis confirms the PPBFL scheme’s theoretical robustness. Comprehensive evaluations across multiple datasets validate the framework’s operational efficiency and defensive capabilities.